A systematic bibliometric review of the United Nation’s SDGS: Which are the most related to higher education institutions? - Muhammad Ashraf, Fauzi; Abdul Rahimi, Abdul Rahman; Lee, Chia Kuang (Emerald Publishing Limited, 2022)
Purpose: This study aims to provide the current and future state of United Nations’ Sustainable Development Goals (SDGs) in the higher education institutions (HEIs). Since the SDGs’ proliferation, HEIs have played a crucial part in meeting the goals. Despite the central role of HEIs in accomplishing the SDGs, there has been little attention in providing a comprehensive overview of the SDGs in relation to HEIs. Design/methodology/approach: A total of 280 publications in the Web of Science database were analyzed through a bibliometric approach consisting of citation analysis, co-citation analysis and co-occurrence of keywords analysis. This review explores the current state of SDGs, its central themes of research streams and predicts future direction in the context of HEIs. Findings: The findings would assist stakeholders to strategize the SDGs on HEIs, including the government and policymakers, university top management, benefactors and academics. Three main research streams were observed sustainable curriculum; challenges and barriers of SDGs; and COVID-19 and health management. Research limitations/implications: Implications suggest that to achieve the stipulated goals in the SDGs, proper planning and strategy should be aligned proportionate to the national agenda. Originality/value: This paper presents a novel knowledge structure by mapping the most relevant SDGs in the context of HEIs based on bibliometric analysis.